2018
DOI: 10.1038/nm.4481
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue thermogenic adaptation requires Nrf1-mediated proteasomal activity

Abstract: Adipocytes possess remarkable adaptive capacity to respond to nutrient excess, fasting or cold exposure, and thus are an important cell type to maintain proper metabolic health. While the endoplasmic reticulum (ER) is a critical organelle for cellular homeostasis, the mechanisms that mediate adaptation of the ER in adipocytes to metabolic challenges are unclear. Here, we show that brown adipose tissue (BAT) thermogenic function requires an adaptive increase in proteasomal activity to secure cellular protein qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
221
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(246 citation statements)
references
References 72 publications
11
221
0
Order By: Relevance
“…In addition, BAT of the CLtreated group showed smaller lipid droplets (Fig. 6D), as reported previously [44,45]. These results indicate that the CL treatment had beneficial effects on HFDinduced obesity, and that the effects of the treatment were associated with the induction of UCP1 expression in BAT.…”
Section: Ucp1-mrfp1 Bac Tg Mice Can Be Used To Track Sequential Changsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, BAT of the CLtreated group showed smaller lipid droplets (Fig. 6D), as reported previously [44,45]. These results indicate that the CL treatment had beneficial effects on HFDinduced obesity, and that the effects of the treatment were associated with the induction of UCP1 expression in BAT.…”
Section: Ucp1-mrfp1 Bac Tg Mice Can Be Used To Track Sequential Changsupporting
confidence: 89%
“…6A) and significantly lower plasma triglyceride concentrations (Fig. 6D), as reported previously [44,45]. In BAT, Ucp1 and mRfp1 mRNA expression levels were higher in the CL-treated group (Fig.…”
Section: Ucp1-mrfp1 Bac Tg Mice Can Be Used To Track Sequential Changsupporting
confidence: 88%
“…Nrf1 is considered to play a key role in cellular responses to stress and ablation of this protein in white adipocytes leading to reduced adipose tissue mass which is in keeping with the phenotype here reported in p107‐ablated mice although they also exhibited a marked insulin resistance in contrast to our ablated p107‐mice. Indeed the overexpression of Nrf1 in BAT resulted in improved insulin sensitivity …”
Section: Discussionmentioning
confidence: 99%
“…Correlation between mRNA-protein pairs is less consistent in transcripts or proteins that decrease after mild or severe cold acclimation ( Fig 3C), which may suggest regulation via protein translation or degradation. Indeed, a recent study found that proteasomal activity increases in cold-adapted BAT, and is important for effective thermogenesis 17 . Unlike at the protein level, there was no increase in transcripts encoding for inner or outer mitochondrial membrane, or ETC proteins, relative to mitochondrial matrix proteins after cold acclimation ( Fig 3E).…”
Section: Overlap Between the Cold-induced Transcriptome And Proteomementioning
confidence: 99%